Molecular Imaging of Lower Extremity Peripheral Arterial Disease: An Emerging Field in Nuclear Medicine - Stacy, Mitchel R. (Frontiers in Medicine, 2022)
Peripheral arterial disease (PAD) is an atherosclerotic disorder of non-coronary arteries that is associated with vascular stenosis and/or occlusion. PAD affecting the lower extremities is characterized by a variety of health-related consequences, including lifestyle-limiting intermittent claudication, ulceration of the limbs and/or feet, increased risk for lower extremity amputation, and increased mortality. The diagnosis of lower extremity PAD is typically established by using non-invasive tests such as the ankle-brachial index, toe-brachial index, duplex ultrasound, and/or angiography imaging studies. While these common diagnostic tools provide hemodynamic and anatomical vascular assessments, the potential for non-invasive physiological assessment of the lower extremities has more recently emerged through the use of magnetic resonance- and nuclear medicine-based approaches, which can provide insight into the functional consequences of PAD-related limb ischemia. This perspectives article specifically highlights and discusses the emerging applications of clinical nuclear medicine techniques for molecular imaging investigations in the setting of lower extremity PAD.